(untitled) (Islas, 2026)
Introduction: This article analyzes the office of chapel master in the territory of the Royal Audiencia of Quito during the colonial period (1534–1830) from the perspective of the social history of music. The study proposes a decentralized approach that incorporates cathedrals, convents, and parish churches, both urban and rural. This broader perspective makes it possible to address the institutional, socioethnic, and functional diversity of the position, as well as to understand the chapel master not only as a musician but also as a social, pedagogical, and economic agent within the colonial order. Methods: The research is grounded in the heuristic method characteristic of historical musicology, complemented by contextual, hermeneutic, and content analysis. Unpublished primary sources from cathedral, conventual, parish, and national archives are examined. The qualitative analysis made it possible to identify patterns related to the functions performed, socioethnic affiliation, institutional mobility, and legal conflicts associated with the exercise of the office. Results: The findings reveal a marked differentiation according to the type of institution. While cathedrals predominantly employed chapel masters of Spanish, Creole, or mestizo origin, smaller urban parishes and especially rural ones were sustained primarily by Indigenous musicians. The study confirms the broad functional scope of the position, which included musical, educational, administrative, and political responsibilities, as well as recurrent practices of multiple jobholding, salary precariousness, and conflicts with civil and ecclesiastical authorities. Conclusions: The study demonstrates that colonial religious musical practice was dynamic and heterogeneous, and that the chapel master played a central role as a social mediator in contexts of structural inequality. The research expands knowledge about Indigenous musicians and territories that have received limited attention in Ecuadorian historiography, and proposes new directions for comparative and prosopographical studies on music, society, and power in the South American colonial sphere.